Some considerations for the developmental origin of the principle of fairness. Issue 6 (7th June 2022) - Geraci, Alessandra
Abstract: The principle of fairness is very important in social life and plays an important role in socio‐moral evaluation; in the last decade, the amount of research on this topic is increasing and suggests different considerations about its origin whether this principle is present at birth or constructed later in development. This article presents some of these considerations focused on the common aspects of innatist and constructivist views and sheds light on the role of experience. The conclusions suggest a more integrated approach, supporting that experience seems to instantiate and model an abstract representation that can be presumably innate. The pursuit of this approach could help researchers to address questions in the field.